2022
DOI: 10.1111/nan.12864
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of miR‐543 in Parkinson's disease: Impact on the neuroprotective gene SIRT1

Abstract: Aims: Parkinson's disease (PD) is a progressive and age-dependent neurodegenerative disease characterised clinically by a variety of motor symptoms and cognitive impairment. PD was initially considered to be a grey matter disease; however, recently, evidence has emerged that white matter changes in PD precede the neuronal loss seen in the grey matter. The cause of these initial white matter changes is yet to be elucidated. Here, we explored whether dysregulated miRNAs and their target mRNA could provide insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Pathways involving some of the identified miRNAs include cell cycle regulation, apoptosis, axon guidance, neurogenesis, synaptic function, inflammation, oxidative stress, metabolism, ubiquitin/proteasome pathway, endocytosis and cell signaling (including insulin, NF-κB, p53 and mTOR) [ 127 , 134 , 136 , 138 , 149 , 150 ]. Interestingly, Ravanidis et al found that certain processes (including ubiquitin-mediated proteolysis, circadian rhythm and axon guidance) are implicated in idiopathic but not genetic ( SNCA or GBA1 ) PD cases [ 151 ].…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…Pathways involving some of the identified miRNAs include cell cycle regulation, apoptosis, axon guidance, neurogenesis, synaptic function, inflammation, oxidative stress, metabolism, ubiquitin/proteasome pathway, endocytosis and cell signaling (including insulin, NF-κB, p53 and mTOR) [ 127 , 134 , 136 , 138 , 149 , 150 ]. Interestingly, Ravanidis et al found that certain processes (including ubiquitin-mediated proteolysis, circadian rhythm and axon guidance) are implicated in idiopathic but not genetic ( SNCA or GBA1 ) PD cases [ 151 ].…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…This is because the makeup of circulating miRNA may change as a result of RNA released during coagulation (Wang et al, 2012). In PD, several miRNAs are expressed differently compared to healthy individuals (Ma et al, 2016; Scheper et al, 2023). miRNAs have roles in the modulation of SNCA, PRKN (Parkin) and PTEN Induced Kinase 1 (PINK1), which are all involved in PD development.…”
Section: Introductionmentioning
confidence: 99%